Libra Announcement: Does it have an Impact on Bitcoin's Price? - Dhekra Azouzi; Abdelghani Echchabi (Journal of Innovation in Business and Economics, 2019)
The main objective of the current study is to investigate the potential effect that the announcement of Libra, a new Facebook cryptocurrency might have on the Bitcoin prices. Accordingly, an event study analysis was applied to achieve the mentioned objective. The findings revealed that the news announcement had no effect on Bitcoin price changes. This indicates that Bitcoin's investor thinks Libra is not a potential competitor of Bitcoin.